The Trickle-Down Effect of Authoritarian Leadership on Unethical Employee Behavior: A Cross-Level Moderated Mediation Model - Rui, Jiang; Qi, Lin Xin (Frontiers in Psychology, 2021)
Benevolent leadership is of great significance to Chinese organizations. Meanwhile, unethical employee behavior also widely exists in all types of social organizations. The relationship between benevolent leadership and unethical employee behavior is worth studying. This paper studies how moral manager (senior leader) leadership trickles down to unethical employee behavior through moral supervisor (employee direct supervisor) leadership, and discusses the moderating effect of LMX and ethical climate. Through the questionnaire survey of 406 pairs of leaders and employees, the research results of multilevel path analysis show that: (1) Moral manager leadership is negatively related to unethical employee behavior. (2) Moral supervisor leadership mediates the relationship between moral manager leadership and unethical employee behavior. (3) LMX positively moderates the relationship between moral manager leadership and moral supervisor leadership, and moderates the mediating effect of moral supervisor leadership. (4) Ethical climate positively moderates the relationship between moral supervisor leadership and unethical employee behavior, and moderates the mediating effect of moral supervisor leadership.